2007
DOI: 10.1007/s00442-006-0654-2
|View full text |Cite
|
Sign up to set email alerts
|

When carnivores are “full and lazy”

Abstract: Are animals usually hungry and busily looking for food, or do they often meet their energetic and other needs in the 24 h of a day? Focusing on carnivores, I provide evidence for the latter scenario. I develop a model that predicts the minimum food abundance at which a carnivore reaches satiation and is released from time constraints. Literature data from five invertebrate and vertebrate species suggest that food abundances experienced in the field often exceed this threshold. A comparison of energetic demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 54 publications
1
70
3
Order By: Relevance
“…A recent study, however, suggests that the assumption that predators are normally energy-limited is likely to be an over-simplification [46]. In almost 90 per cent of the vertebrate species examined, the kill rates of prey exceeded the energetic demands of the predators, suggesting that energy intake in predators is unlikely to be as limiting as once believed.…”
Section: Results (A) Effects Of Lipid and Protein Intake On Egg Produmentioning
confidence: 97%
“…A recent study, however, suggests that the assumption that predators are normally energy-limited is likely to be an over-simplification [46]. In almost 90 per cent of the vertebrate species examined, the kill rates of prey exceeded the energetic demands of the predators, suggesting that energy intake in predators is unlikely to be as limiting as once believed.…”
Section: Results (A) Effects Of Lipid and Protein Intake On Egg Produmentioning
confidence: 97%
“…Comparing kill rates in number of ungulates/week suggests that pumas exhibit strong seasonal variation, whereas comparing kill rates in kg/day suggests that regardless of number of animals killed per unit time, pumas kill an equivalent amount of meat. Kill rates in kg/day suggest that pumas might be following or meeting some energetic threshold irrespective of prey availability (Jeschke 2007). However, when observing the kill-rate metrics together, they point to the complexity of predator-prey relationships in a multipredator system.…”
Section: Discussionmentioning
confidence: 97%
“…If digestion-limitation indeed occurs much more often than collection-limitation (Jeschke et al, 2002;Jeschke, 2007), then food quality may be a much more important factor controlling habitat quality than, for example, food density. When digestion-limited, animals can't get a higher food intake at a higher food density, whereas they can at a higher food quality (Van Gils et al, 2006b).…”
Section: Please Scroll Down For Articlementioning
confidence: 97%
“…by contrast, a forager is digestion-limited when digestion cannot keep up with the rate at which food is collected. This usually occurs when food is abundant and handling time is negligible (Jeschke, 2007). Recently, Jeschke et al, (2002) suggested that digestion-limited foraging is much more widespread than collection-limited foraging.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%